Pendidikan Tasawuf Perspektif Hadratus Syaikh K.H. Muhammad Hasyim Asy’ari - Nurul Izzah, Dewi; ., Jasminto (Jurnal Spiritual Healing, 2024)
The reform or modernization movement has gradually led the Muslim community to depart from the pure teachings of the religion of Islam, such as the knowledge of Sufism. Classical Islamic teachings are perceived as outdated and antiquated. However, by abandoning the pure teachings of Islam, the Muslim community will only become more left behind and lose touch with their own identity. Hadratus Syaikh KH. Muhammad Hasyim Asy'ari was one of the scholars who opposed this modernization movement through the Sufi education he taught. Hadratus Syaikh wrote the basic concepts of Sufi knowledge in his books, such as Adāb al-'Ālim wa al-Muta'alim, Haẓihi ar-Risālah Jāmi'at al-Maqāṣid, Risālah ad-Durar al-Muntaṡiroh fī al-Masāil at-Tis'a 'Asyrah, Tamyīz al-Ḥaq min al-Bāṭil, and Risālah fī at-Taṣawuf. This research is a literature study that examines five books written by Hadratus Syaikh KH. Muhammad Hasyim Asy'ari. The research findings reveal that the Sufi education of Hadratus Syaikh KH. Muhammad Hasyim Asy'ari represents Sunni or Ethical Sufism, which utilizes the teachings of Tazkiyatun Nafs (purification of the soul) and Tarbiyah Ruhaniyah (spiritual education). The result is a balance between the spiritual and the ritual aspects. This concept of Sufi education needs to be taught in every educational institution to shape the character of students, as it is highly relevant to the current era of character education. Keywords: Sufism, Education, Hasyim Asy'ari